Evaluation of the Effectiveness of Village Fund Allocation (ADG) Management in Community Empowerment: Qualitative-Descriptive Study - Julfikar, Julfikar; Fuad, Muhammad; Rizal, Muhammad (Doctoral Program of Social Science Pasundan University, 2025)
The purpose of this study was to determine the effectiveness of the management of Village Fund Allocation (ADG) in community empowerment.The location of the study wasin Alur Itam Village, Birem Bayeun District, East Aceh Regency. This descriptive-qualitative study used data analysis methods based on the procedures of Miles et al. (2014), namely data reduction, data presentation, and verification and drawing conclusions. Key informants included Geuchik (Head of Village), Finance and Development Head of Village; while supporting informants were Tuha Peut (BPD) and the Head of Youth of Alur Itam Village. Primary data were collected through interviews, observations and documentation. The results identified factors that hindered the effectiveness of the management of village fund allocation in community empowerment at the research site, namely the lack of community participation, especially youth, in Village Deliberations related to the planning of ADG use; the dominance of decisions by village officials and community leaders; limited human resources; fund allocation that focuses more on infrastructure; and, lack of transparency and supervision over ADG management.